2002
DOI: 10.1081/jdi-120015679
|View full text |Cite
|
Sign up to set email alerts
|

THE IMPACT OF NASAL CARRIAGE OF METHICILLIN-RESISTANT AND METHICILLIN-SUSCEPTIBLESTAPHYLOCOCCUS AUREUS(MRSA & MSSA) ON VASCULAR ACCESS-RELATED SEPTICEMIA AMONG PATIENTS WITH TYPE-II DIABETES ON DIALYSIS

Abstract: Diabetic type-II S. aureus nasal carriers on HD through CVCs make an extremely high-risk group for MSSA and MRSA nasal carriage-related VRS. The incidence of S. aureus nasal carriage-related VRS could reasonably be reduced through a challenging obligation of optimizing AVF prevalence in this high-risk group, while limiting the use of CVCs, at the same time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 28 publications
3
27
2
1
Order By: Relevance
“…Long-term hemodialysis patients, especially the elderly and diabetics, are more likely to be Staphylococcus aureus nasal carriers (up to 60%) (9)(10)(11) and are at a higher risk of infection due to dissemination of bacteria from nose to hands and beyond (10,11).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Long-term hemodialysis patients, especially the elderly and diabetics, are more likely to be Staphylococcus aureus nasal carriers (up to 60%) (9)(10)(11) and are at a higher risk of infection due to dissemination of bacteria from nose to hands and beyond (10,11).…”
Section: Risk Factorsmentioning
confidence: 99%
“…We used a Cox proportional hazard model to assess the effect of MRSA carriage on the study end points. Unadjusted hazard ratios were further adjusted in regression models by adding prespecified variables: age, gender, as well as the covariates (vascular access type, the presence of diabetes, recent hospitalization, recent use of antibiotics, and serum albumin level) that have been reported to have an association with MRSA carriage or infection in dialysis populations (4,13,14,22,23). All of the tests were two-tailed with significance defined by P values of less than 0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, the bulk of evidence concerning the risk of MRSA nasal carriage was limited to hospitalized patients. There were very few studies addressing the clinical effect of MRSA nasal carriage on hemodialysis (HD) patients, most of whom were freely ambulatory in the general community (4,13,14). For the establishment of public health intervention policy in this vulnerable population, we were interested in determining the effect of MRSA nasal carriage on all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies generally also point to colonization with S aureus as a risk for HD-related BSI (6,11). The relative roles of other factors such as poor hygiene (8), iron storage levels (12), immunosuppression (6), diabetes mellitus (11,12) and low albumin remain to be defined (13).…”
Section: N a Previous Issue Of The Canadian Journal Of Infectiousmentioning
confidence: 99%
“…Studies generally also point to colonization with S aureus as a risk for HD-related BSI (6,11). The relative roles of other factors such as poor hygiene (8), iron storage levels (12), immunosuppression (6), diabetes mellitus (11,12) and low albumin remain to be defined (13). Two studies (7,10) found that BSI rates varied substantially among dialysis centres, suggesting that being dialyzed at a particular centre may increase the risk for an HD-related BSI and that surveillance results may be used for quality improvement.…”
Section: N a Previous Issue Of The Canadian Journal Of Infectiousmentioning
confidence: 99%